Metaphor of ‘progress’: A metaphoric rhetorical criticism on Aminuddin Baki's Torch Movement speech 2 - Sayed Halem Shah, Dil Froz Jan; Ibrahim, Faridah; Yunus, Norzita; Ahmad, Abdul Mua’ti bin; Hassan, Hamisah; Shamshudeen, Rosya Izyanie (Elsevier Ltd., 2014)
This paper looks at the Aminuddin Baki's Torch Movement Speech 2 from the metaphorical perspective. The objective of the study is to identify the type of metaphors employed and how the metaphors are conveyed in the Speech.Numerous studies have been done on the biographical portion of Aminuddin Baki but none on all his Torch Movement speeches that he had made on the progression of the natives in Malaysia at that time.This study used a qualitative method through Neo-Aristotelian Criticism perspective in the analysis of speech. This study demonstrates the relevance of ancient Malay metaphor in modern day communication interaction.